(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The resettlement of Bukidnon following its separation from the Misamis province in 1907 was formalized under the Special Provincial Governmental Act, also known as Act 1693. This transition sparked various resistance movements within the province, including the Tauidis outlaws and the Tungud movement, both formed to oppose America’s resettlement campaign in Bukidnon. After its suppression by the constabulary the American administration introduced an education system aimed at pacifying the Bukidnon population while fostering economic self-sufficiency in the province. This paper aims to analyze and evaluate the role of the education system in Bukidnon as a crucial component of America’s pacification and integration campaign in the province. It addresses key questions such as: How did the America introduce education in Bukidnon? What were the education policies implemented by America in the region? And what impact did education have on the economic and political integration of Bukidnon? The study uses an archival approach, relying on primary sources including the Reports of the Director of Education from 1906 to 1938, as well as the Annual Reports of the Philippine Commission, the Report of the Auditor of the Philippines, and the Annual Report of the Governor General of the Philippine Islands. These sources offer a descriptive and narrative account of education in Bukidnon within the broader context of America’s campaign of pacification and integration. This research is significant as it rationalizes the impact of America’s education on the agricultural systems and food production in the province. By examining the development of the education system, this study contributes to a deeper understanding of the dynamics of colonial governance and its impact on local communities.